Complete plastome sequence of Stauntonia obovatifoliola subsp. urophylla (Lardizabalaceae) - Hua-Min Huang; Kun-Kun Zhao; Hong-Xin Wang; Zhi-Xin Zhu; Hua-Feng Wang (Mitochondrial DNA. Part B. Resources, 2019)
Stauntonia obovatifoliola subsp. urophylla belongs to Lardizabalaceae. It is woody vine, with fine lines on its stems, branches, and petioles. In China, they are mainly distributed in Fujian, Guangdong, Guangxi, Jiangxi, Hunan, and Zhejiang. Here, we report and characterize the complete plastid genome sequence of S. obovatifoliola subsp. urophylla in an effort to provide genomic resources useful for promoting its systematics research. The complete plastome of S. obovatifoliola subsp. urophylla is 158,944 bp in length, including two Inverted Repeat (IR) regions of 26,284 bp, a Large Single-Copy (LSC) region of 87,306 bp and a Small Single-Copy (SSC) region of 19,070 bp. The plastome contains 115 genes, consisting of 80 unique protein-coding genes, 31 unique tRNA genes, and four unique rRNA genes. The overall A/T content in the plastome of S. obovatifoliola subsp. urophylla is 61.40%. The complete plastome sequence of S. obovatifoliola subsp. urophylla will provide a useful resource for the conservation genetics of the species as well as for the phylogenetic studies of the genus Stauntonia.